Effects of Sheet Resistance on mc-Si Selective Emitter Solar Cells Using Laser Opening and One-Step Diffusion - Sheng-Shih Wang; Jyh-Jier Ho; Jia-Jhe Liou; Jia-Show Ho; Song-Yeu Tsai; Hsien-Seng Hung; Chi-Hsiao Yeh; Kang L. Wang (International Journal of Photoenergy)
In order to simplify process procedure and improve conversion efficiency (η), we present new steps of laser opening and one-step POCl3 diffusion to fabricate selective emitter (SE) solar cells, in which heavily doped regions (HDR) and lightly doped regions (LDR) were formed simultaneously. For HDR, we divided six cells into two groups for POCl3 diffusion with sheet resistance (RS) of 40 Ω/sq (for group A) and 50 Ω/sq (for group B). The dry oxidation duration at a temperature of 850°C was 18, 25, and 35 min for the 3 different cells in each group. This created six SE samples with different RS pairings for the HDR and LDR. The optimal cell (sample SE2) with RS values of 40/81 Ω/Sq in HDR/LDR showed the best η of 16.20%, open circuit voltage (VOC) of 612.52 mV, and fill factor (FF) of 75.83%. The improvement ratios are 1.57% for η and 14.32% for external quantum efficiency (EQE) as compared with those of the two-step diffusion process of our previous study. Moreover, the one-step laser opening process and omitting the step of removing the damage caused by laser ablation especially reduce chemistry pollution, thus showing ecofriendly process for use in industrial-scale production.